Classificação de imagens em áreas cultivadas com citrus por técnicas de sensoriamento remoto e geoestatística - Silva, Alessandra Fagioli da [UNESP]; Zimback, Celia Regina Lopes [UNESP]; Landim, Paulo Milton Barbosa [UNESP] (EIA Energy in Agriculture, 2012)
The objective of this study was to compare the accuracy for methods of classifying satellite images to determine areas planted with citrus in Bauru and the Araraquara mesoregion, through methods of geostatistical analysis and remote sensing for the breakdown and qualification of the area planted. The area used for the research in this study is located in the central region of the state of São Paulo, with an area of ​​56,146.78 hectares. We used the GIS-SPRING for processing the data. We used the digital image bands 2, 3 and 4 from the CBERS 2B satellite, CCD camera (High Resolution Imagery Camera) on the date of 04/16/2009, at orbit sections 157/124 and 157/125. Two classification methods were supervised in the process of classifying images with the GML (Maximum Likelihood) and KI (Kriging Indicative), in addition to the classification screen taken as ground truth. The Trusts classifications were evaluated by Kappa. The classifiers obtained are better for classification in larger areas of citrus. The Kriging Indicative unified the small areas of citrus in a single area; the kriging was the classifier that less classified citrus riparian area; already pretty substantially MAXVER kills ciliary with citrusvalidating the Kriging was indicative that the classifier obtained the lowest quality rating compared to MAXVER and a longer processing time, the MAXVER showed the total citrus area closest to the ground truth, while Kriging was indicative that the classifier overestimated the total citrus area in 27.94%.

O objetivo deste trabalho foi comparar a precisão de métodos de classificação de imagens orbitais na determinação de áreas cultivadas com citros, na Mesoregião de Bauru e Araraquara, através de métodos de sensoriamento remoto e geoestatísticos, para a discriminação e quantificação da área plantada. A área de estudo utilizada nesta pesquisa esta localizada na região central do Estado de São Paulo, com uma área de 56.146,78 ha. Foi utilizado o SIG-SPRING para o processamento dos dados. Foram utilizadas as bandas 2, 3 e 4 da imagem digital proveniente do satélite CBERS 2B, câmera CCD (Câmera Imageadora de Alta Resolução) da data de 16/04/2009, nas órbitas/ponto 157/124 e 157/125. No processo de classificação das imagens foram estudados dois métodos de classificação supervisionada, sendo o MAXVER (Máxima Verossimilhança) e a KI (Krigagem Indicativa), além da classificação em tela tida como verdade terrestre. As fidedignidades das classificações foram avaliadas pelo índice Kappa. Os classificadores obtiveram melhor qualidade de classificação para as áreas maiores com citros; a Krigagem Indicativa unificou as áreas pequenas de citros em uma única área; a Krigagem Indicativa foi o classificador que menos classificou área de mata ciliar como citros, já o MAXVER confundiu consideravelmente mata ciliar com citros; pela validação, a Krigagem Indicativa foi o classificador que obteve a menor qualidade de classificação em comparação com o MAXVER e o maior tempo de processamento; o MAXVER foi o que apresentou área total de citros mais próxima da verdade terrestre, enquanto que a Krigagem Indicativa foi o classificador que mais superestimou a área total de citros em 27,94 %.
Image classification in areas cultivated with citrus by remote sensing and geostatistical techniques
Keywords: Application technology; Drift; Average volumetric diameter (VMD); Krigagem indicativa; Satélite CBERS 2B; Classificadores de imagens